2009
DOI: 10.1111/j.1834-7819.2008.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal therapy on serum TNF‐α and HbA1c levels in type 2 diabetic patients

Abstract: Background: To determine the effect of non-surgical periodontal therapy on serum TNF-a and HbA1c levels in poorly and well-controlled type 2 diabetic patients. Methods: In total, 45 patients were enrolled in the study; 30 patients with type 2 diabetes mellitus with periodontitis (15 with poorly controlled diabetes, HbA1c ‡ 7%, group 1A and 15 with well-controlled diabetes, HbA1c < 7%, group 1B) and 15 patients that were systemically healthy with periodontitis (group 2). The plaque index, gingival index, probin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…Therefore, it was suggested that periodontal treatment is effective in improving metabolic control in patients with T2DM, possibly through reduction in the serum concentration of TNF-α and decreased insulin resistance. Though some studies have shown improved glycemic control with periodontal treatment in T2DM patients through reduction of peripheral TNF-α concentrations [37, 38], no reduction in serum TNF-α levels has been found following periodontal therapy in T2DM patients in other studies [39, 40]. However, a recent systematic review found that periodontal treatment reduced serum levels of TNF-α and CRP in T2DM patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that periodontal treatment is effective in improving metabolic control in patients with T2DM, possibly through reduction in the serum concentration of TNF-α and decreased insulin resistance. Though some studies have shown improved glycemic control with periodontal treatment in T2DM patients through reduction of peripheral TNF-α concentrations [37, 38], no reduction in serum TNF-α levels has been found following periodontal therapy in T2DM patients in other studies [39, 40]. However, a recent systematic review found that periodontal treatment reduced serum levels of TNF-α and CRP in T2DM patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have reported an increased concentration of TNF-α in GCF in activated periodontal locations, and decreased concentrations following periodontal treatment. It has also been found that periodontal treatment is followed by a notable decrease in HbA1c levels in T2DM patients (46,47). In this study, we examned the correlation of GCF vaspin and omentin 1 levels with the GCF levels of TNF-α, because TNF-α has a recognizable pro-inflammatory impact on CP and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies of the effect of nonsurgical periodontal treatment in diabetic patients generally show improved periodontal status, while results concerning changes in glycemic status are rather contradictory. Some found significant improvements in glycemic control (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); others did not (20)(21)(22)(23)(24)(25)(26). Meta-analyses of intervention studies indicate a need for additional trials to clarify this relationship (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%